Factors Influencing the Adoption of E-Health Management among Saudi Citizens with Moderating Role of E-Health Literacy - Alshammari, Waleed Mansi G; Alshammari, Fahad Maiyah M; Alshammry, Faiz Mayah M (Information Management and Business Review, 2021)
This study aimed to examine the role of internet access, social influence, facility access, and cost concerns on E-health adoption in Saudi Arabia with moderating role of E-health literacy. Saudi citizens were the targeted population of this study. To fulfill the objectives of this study, quantitative research methods with a cross-sectional technique were applied. A self-administrative survey was employed with a questionnaire to collect the data. This study used the purposive sampling method for the collection. Structure equation modeling was applied by using Smart PLS 3 to analyze the data. The findings of the current study show that internet access, social influence, and facility access have significant and positive effects on E-health adoption. Cost concerns have a significant and negative influence on the Adoption of E-Health Management services. Results revealed that E-health literacy has a significant and positive moderating role in the association of internet access, facility access, and cost concerns on E-health adoption. Results of this study contribute to the body of literature by finding that internet access, social influence, facility access, and cost concerns have a significant effect on the Adoption of E-Health Management services and E-health literacy is essential to improve the Adoption of E-Health Management services